ChemInform Abstract: Highly Diastereo‐ and Enantioselective Organocatalytic One‐Pot Sequential 1, 4‐Addition/Dearomative‐Fluorination Transformation. Issue 14 (20th March 2013) - Li, Feng; Sun, Long; Teng, Yuou; Yu, Peng; Zhao, John Cong‐Gui; Ma, Jun‐An
Abstract This reaction yields products with adjacent tertiary and quarternary stereocenters in good yields with high diastereo‐ and enantioselectivities.